KEY COMPONENTS OF TECHNICAL PREPARATION IN TABLE TENNIS - Kholmatov Bekzod Uralovich (Web of Journals Publishing, 2024)
Present article is devoted to the main key components of technical preparation in table tennis. All components have been given clearly by the table. Technical preparation focuses on developing the fundamental skills and techniques that enable players to execute strokes, movements, and strategies effectively during matches.
Keywords: Grip, shakehand, Penhold grip, Stance and Positioning, Stroke Technique, Footwork, Tactical Awareness, Mental Preparation, Practice Drills, Equipment Familiarity.